Estimation of hydraulic conductivity by using pumping test data and electrical resistivity data in faults zone - Debao Lu (Elsevier, 2021)
Obtaining hydraulic properties is crucial for describing the transport of groundwater and pollutants in the faults area. In this way, the spatial distribution of hydraulic conductivity plays a major role in expressing the heterogeneous flow and non‐Fickian behavior of solute transport which both are common in nature. However, the existing methods are focusing on obtain the mean value (1D) of the aquifer’s hydraulic conductivity, and there are certain challenges in obtaining the spatial distribution (2D) of the hydraulic conductivity. Thus, in this study, a novel method was proposed that combines electrical resistivity tomography (ERT) with pumping test data to obtain the spatial distribution of hydraulic conductivity for metamorphic rock and granite fault zone in the Xinchang region of Beishan, China. The hydraulic conductivity of an aquifer was obtained using data from 30 pumping tests for seven pumping wells, and the results were fitted using the ERT and used to determine the aquifer resistivity at the respective positions. The measured resistivity and hydraulic conductivity were fitted to obtain a correlation (R-K). The hydraulic conductivity for metamorphic rock with a small hydraulic conductivity was better fit by an exponential (R2 = 0.97) than a linear or power law. The hydraulic conductivity calculated using the R-K correlation has an error of less than 10.50% compared with that measured by pumping tests, and the Nash-Sutcliffe efficiency coefficient is 0.96. The superior accuracy of the results obtained using the proposed method was confirmed by comparison with the results obtained using two established methods. The 2-D hydraulic conductivity distribution of the fault zone is potential for accurate and low-cost descriptions of groundwater and pollutant transport in the fault zone with strong heterogeneity.